Pengaruh Pengalaman Kerja dan Tingkat Pendidikan terhadap Prestasi Kerja Karyawan pada PT. Amrtha Micro Fintec Cabang Wewiku Kabupaten Malaka - Ewaldus Erwin Leki; Rolland E. Fanggidae; Yonas F. Riwu (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the effect of work experience and education level on employee performance at PT Amartha Mikro Fintec Wewiku Branch, Malaka Regency. The research employed a quantitative approach using an associative research design to analyze the relationship between the independent variables and the dependent variable. The study population consisted of all 35 employees of the company, and a saturated sampling technique was applied, meaning that all members of the population were selected as research participants. Data were collected through questionnaires and analyzed using SPSS version 22. The findings indicate that work experience has a positive and significant effect on employee performance. Likewise, education level also has a positive and significant influence on employee performance. Simultaneously, work experience and education level significantly affect employee performance and provide a substantial contribution to explaining variations in employee performance. These findings suggest that employees with greater work experience and higher educational attainment tend to achieve better job performance. Therefore, the company is expected to pay greater attention to work experience and educational background in recruitment, training, and career development programs. Such efforts are expected to improve employee performance more effectively while supporting organizational productivity and the achievement of corporate goals in a sustainable manner.